How to Make an Internal Team Coach: An Integration of Research - Gabriela Fernández Castillo; Rylee Linhardt; Eduardo Salas (Behavioral Sciences, 2024)
Team coaching has been found to increase group effort, improve interpersonal processes, and increase team knowledge and learning. However, the team coaching literature is renowned for its inability to define team coaching itself—making it difficult to solidify its place in the world of team science. So far, there is no consensus on what specific training would serve internal leaders best, and how they would connect to the team coaching literature. We know leadership and team training are effective in improving organizational outcomes, but the gap in the literature lies in identifying what specific competencies internal team coaches need, and what training could fulfill these. In this piece, we seek to (1) identify what competencies internal team leaders need based on the outcomes we know team coaching yields, (2) identify specific behaviors that can fulfill these competencies, and (3) integrate the literature to form an evidence-based guide on what training to provide to internal team coaches. By doing so, we hope to provide a definitive understanding of what internal team coaches need to be successful.